Supplementation with mineral mix or concentrate booster restored fertility in cows following foot-and-mouth disease infection - Aris Puji Nugroho; Ali Agus; Moh. Sofiul Anam; Suherni Susilowati; Herry Agoes Hermadi; Dian Ayu Permatasari; Mohammad Anam Al Arif (Universitas Airlangga, 2025)
This study aimed to evaluate the effects of supplementing mineral mix and concentrate booster on the fertility of cows recovering from foot-and-mouth disease (FMD). Eighteen post-FMD cows were assigned to three treatment groups. Cows in the T0 group received a standard feed consisting of elephant grass and a local concentrate. In the T1 group, cows were provided the standard feed supplemented with 40 g/day of mineral mix, while cows in the T2 group received the standard feed supplemented with 600 g/day of concentrate booster. The feeding treatments were applied for 42 days, and fresh drinking water was provided ad libitum. The results showed that the onset of estrus occurred significantly earlier (p <0.05) compared to the anestrus period experienced during FMD infection. Both supplemented groups exhibited higher (p <0.05) estrus rates, pregnancy rates, and calving rates than the T0 group. The interval between the last estrus and the initiation of additional feeding was considerably longer than the onset of estrus observed after treatment. The pH and ferning scores of cervical mucus in cows from the T0 group were lower than those in the T1 and T2 groups. However, no significant differences (p >0.05) were found in cervical mucus pH or ferning scores between the T1 and T2 groups, between pregnant and non-pregnant cows, or between offspring sex categories. In conclusion, supplementation with either a mineral mix or a concentrate booster improved fertility parameter, including estrus rate, pregnancy rate, and calving rate, in cows recovering from FMD.